Phenol and phenolic compounds toxicity - Abd Gami, Afilah; Abd. Shukor, Mohd. Yunus; Abdul Khalil, Khalilah; Dahalan, Farrah Aini; Khalid, Ariff; Ahmad, Siti Aqlima (Hibiscus Publisher, 2014)
The present of phenol and phenolic compound pollutant are the common problems faced by worldwide population due to natural and chemical process that comes from either industrial or human activity. Exceeding the standard level in our environment was not a new issue nowadays especially in developed or developing countries. The study concerning to the phenolic compound was started in the early 1908 where researchers started to look for solution and are interested in phenol-related research due to its toxicity and ability to retain in environment for a long period. Higher level of phenol leakage within the environment can actually affects the whole ecosystem. A toxicological property of phenol has been contributed by the formation of organic and free radical species and also due to its hydrophobicity. The structure of phenol itself shows its reactivity which lead to its properties like persistence in environment, toxicity and the possibilities of carcinogenic properties toward living organism.